PERILAKU BERBASIS KESELAMATAN PADA PELABUHAN PT PENAJAM BANUA TAKA - Lina Yuliana (Program Studi D-IV K3, 2020)
behaviour-based Safety is a tool for observing behaviour to create safe behaviour and prevent work accidents. This study aims to evaluate the behaviour-based Safety program in the observation card program at PT Penajam Banua Taka Harbor. The National Safety Council (NSC) (2011) conducted research which resulted in 88% of the causes of work accidents due to unsafe behaviour, 10% due to unsafe conditions and 2% of unknown causes. PT Denso Indonesia's work accident rate has also decreased by 66.67–88.89% so that BBS activation in the company can be prevented and reduce the incidence of work accidents. Based on preliminary study data, it was obtained that 30% of employees were mature about safety-based programs and 60% reported unsafe action figures. Employees are not yet committed to reporting unsafe action findings and unsafe conditions with the observation card program. This causes the objectives of the behaviour-based Safety Program to prevent work accidents have not been optimally achieved. This research is descriptive quantitative. The population are an employee of the Operational Department of PT Pelabuhan Penajam Banua Taka, the amount of sample is 37 respondents. The sampling technique used is simple random sampling. In the input element, the Sub-element of Critical Safety Determination Behaviour has the highest effectiveness value, which is equal to 78.05%, while the training has the lowest effectiveness value, which is 73.94%. The Observation and Feedback Process element has the highest effectiveness value is the implementation of observations, which is 76.75%. meanwhile, Field / Equipment / System Modification has the lowest effectiveness value, which is 70.27%.